TECHNIQUES TO ENHANCE VOCABULARY THROUGH FAIRY TALES - Ozoda Eshkobilova,; Sevinch Ruziyeva, (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Fairy tales, with their imaginative plots and rich language, provide an engaging and effective medium for enhancing vocabulary skills. This article explores a variety of techniques designed to help students expand their vocabulary by interacting with fairy tales. These techniques include read-aloud sessions, vocabulary journals, context clue exercises, vocabulary games, creative writing, and story sequencing. Each method leverages the rich language of fairy tales to encourage active engagement with new words in both context and usage. Through these strategies, learners not only acquire new vocabulary but also improve their reading comprehension, creative writing, and critical thinking skills. By combining language learning with the timeless appeal of fairy tales, students can develop a deeper, more enjoyable connection with language that supports long-term retention and language mastery.